UTILIZATION OF NATURAL ANTIFOULING COMPOUNDS FROM MANGROVES ON PAYUNG ISLAND, SUNGSANG, SOUTH SUMATERA - Sarno Sarno; Enggar Patriono; Siti Nurbaiti; Nely Puspitasari (BIOVALENTIA: Biological Research Journal, 2022)
Mangrove is a species of high-level plant whose growth is influenced by the tides of seawater. Antifouling is a system used to prevent marine life attached to an object that is submerged in seawater. The use of natural Antifouling is one of the efforts to reduce water and environmental pollution, such as natural Antifouling from the mangrove plants Rhizophora apiculata and Avicennia alba. The study was conducted in Sungsang, South Sumatera, Indonesia. Avicennia marina and Rhizophora apiculata are mangrove plants that are suspected to have Antifouling content, namely tannins, terpenoids, and steroids. This research aims to determine the effect of the addition of the Avicennia marina fraction and the Rhizophora apiculata fraction on oil paints on the area of macrofouling pasting on the test plate, how the effect of adding different Avicennia marina fractions on the sticking of macrofouling on the wood plate. Avicennia marina and Rhizophora apiculata contain secondary metabolite compounds as natural Antifouling that do not pollute the environment and meet the H0 hypothesis rejected and H1 accepted and suspected that there is no macrofouling on the plates that have been tested proven to reduce pasting.